Cover Image. Issue 17 (1st November 2021) - Mikulan, Ezequiel; Russo, Simone; Zauli, Flavia Maria; d'Orio, Piergiorgio; Parmigiani, Sara; Favaro, Jacopo; Knight, William; Squarza, Silvia; Perri, Pierluigi; Cardinale, Francesco; Avanzini, Pietro; Pigorini, Andrea
Abstract : COVER ILLUSTRATION The image presents a high‐definition reconstruction obtained from an MRI that was de‐identified using our novel method. The artwork aims to show that with current techniques it is possible to recreate with outstanding accuracy not only the brain but also the face of a subject, putting privacy at risk. In our study we present a new method, called AnonyMI, and validate it in terms of its de‐identification performance in two behavioral experiments and also using a machine learning face recognition software; always comparing it to other state‐of‐the‐art methods. In addition we performed an analysis of how well each method preserves the geometry of the brain and the head, which is crucial for maximizing data re‐usability. Our results showed that all methods significantly decreased the re‐identification risk, and that AnonyMI was the most performant in terms of the geometrical preservation of the brain and head shapes.